Coupling of neighbouring low voltage residential distribution feeders for voltage profile improvement using power electronics converters - Shahnia, Farhad; Ghosh, A. (The Institution of Engineering and Technology, 2016)
© The Institution of Engineering and Technology 2016. Low voltage feeders (LVFs) experience several voltage quality (VQ) issues such as voltage drop at network peak periods, voltage rise at middays when high number of rooftop photovoltaic cells (PVs) are existing in the feeder, rapid voltage fluctuations as the results of the clouds effects on the power generation of PVs, and voltage unbalance due to the inherent random characteristics of the single-phase loads and PVs. This study addresses these problems by proposing the concept of coupling the neighbouring LVFs. Based on this concept, two or more LVFs of the same distribution transformer or different distribution transformers are interconnected to support each other and minimise the VQ problems. First, the performance of LVFs in the existing form is discussed and three approaches of coupling the LVFs are presented. Among the presented techniques, coupling of LVFs through a distribution static compensator (DSTATCOM) at the end of the feeder is proposed and focused as an effective technique with minimal side effects such as power losses and cost. Proper dynamic control methods are also proposed for the DSTATCOM and the performance of such a system is investigated under steady-state and dynamic conditions via numerical analysis and simulation studies in MATLAB and PSCAD/EMTDC.